Financial Distress Prediction in Subfrastructure, Utility and Transportation Sub Sector Service in Indonesia - Resa Meita Ary Putri; Hadi Paramu; Intan Nurul Awwaliyah (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2020)
The purpose of this study is to examine and analyze whether profitability ratios, liquidity ratios, solvency ratios, cash flow ratios, activity ratios, and cash positions affect the financial distress in service companies in infrastructure, utilities, and transportation sub-sectors in Indonesia. The number of samples of this study are 51 companies and research ranges from 2013-2018. Total observations in this study are 289 out of 306 observations, and the rest are outliers. The method of analysis is using logistic regression analysis. The result shows there are two independent variables ( Cash Flow from Operations to Total Assets and Cash to Current Liabilities ) that have a significant effect on financial distress, while four independent variables ( Return on Equity , Working Capital to Total Assets, Debt Assets Ratio , Sales to Current Assets ) have no significant effect on financial distress.